PENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN MATEMATIKA MENGGUNAKAN MEDIA MANIPULATIF DI SEKOLAH DASAR - Anes, Albanus; Margiati, K.Y.; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract Problem in this study is Is there an increase in student learning outcomes in mathematicsl learning using manipulative media at Elementary School fourth grade 01 Segonde Bengkayang?